Collaborative virtual screening to elaborate an imidazo[1, 2-a]pyridine hit series for visceral leishmaniasis. Issue 3 (21st January 2021) - Akao, Yuichiro; Canan, Stacie; Cao, Yafeng; Condroski, Kevin; Engkvist, Ola; Itono, Sachiko; Kaki, Rina; Kimura, Chiaki; Kogej, Thierry; Nagaoka, Kazuya; Naito, Akira; Nakai, Hiromi; et al.
Abstract : Ligand-based similarity screening of proprietary pharmaceutical company libraries enables rapid hit to lead investigation of a chemotype with anti- leishmania activity. Abstract : An innovative pre-competitive virtual screening collaboration was engaged to validate and subsequently explore an imidazo[1, 2- a ]pyridine screening hit for visceral leishmaniasis. In silico probing of five proprietary pharmaceutical company libraries enabled rapid expansion of the hit chemotype, alleviating initial concerns about the core chemical structure while simultaneously improving antiparasitic activity and selectivity index relative to the background cell line. Subsequent hit optimization informed by the structure–activity relationship enabled by this virtual screening allowed thorough investigation of the pharmacophore, opening avenues for further improvement and optimization of the chemical series.